Discrepancies between the Intentions and Behaviour of Farm Operators in the Contexts of Farm Growth, Decline, Continuation and Exit - Evidence from Estonia - Ants-Hannes Viira; Anne Pod̈er; Rando Var̈nik (German Journal of Agricultural Economics (GJAE), 2014)
A considerable body of research on farmers' behaviour is based on the surveys regarding their behavioural intentions. The theory of planned behaviour states that while the formation of intentions normally precedes behaviour, several factors affect the realisation of the intended behaviour. Therefore, the usefulness of ex-ante surveys for predicting farmers' behaviour requires more attention to reduce the potential biases in such analyses. The paper investigates how well the farmers' intentions correspond with the behaviour in cases of farm exits, continuation of farming and farm size changes in Estonia. Based on the farm survey in 2007, the follow-up survey in 2011, and paying agency's registry data, the ex-ante data on the intentions is combined with ex-post data on actual behaviour. A recursive bivariate probit regression is used to study the effects of selected socioeconomic characteristics on the probabilities of intended and realised behaviour, and the effects of stated intentions on actual behaviour. The results indicate that the usefulness of intentions in predicting actual behaviour differs, depending on the nature of the question in the farm life cycle context. Intentions are found to be a better predictor of actual behaviour when the considered event is regarded as positive (continuation of farming and farm growth) rather than negative (farm exit or farm shrinkage).
Keywords: 330; Landwirtschaftliche Betriebsform; Unternehmenswachstum; Marktaustritt; Vergleich; Estland